"Art is like a virus that stings you" - (:unkn) unknown (My University, 2021)
Long neglected by the Burkinabè, the objects that make up the repertoire of African art have become the focus of a recent craze among the middle and upper classes of the country's cities. Once magical-religious objects, of power or everyday life, they are now becoming works of art that are no longer only appreciated by their craftsmen, merchants and their usual Western clientele. My thesis is driven by the desire to question the aesthetic experience of African art sought by these professionals and the new buyers on this market, and thus to grasp recent developments in local conceptions of the work and art. I chose to combine a holistic approach to the market, which takes into account the interactions between all the categories of actors involved, with a careful observation of the relationships that people develop with the works in question - regardless of their place in the hierarchy of values (in other words, whether they are "originals" works, or "copies" and the main categories of the latter). I was interested in the way in which opinions of taste are constituted and transmitted, and this, through the prism of the practices of manufacture, sale and exhibition of the pieces. Finally, I show that these objects are nowadays more and more valued by the Burkinabè because they stimulate strong feelings (of fascination and passion, nostalgia but also disgust) and give them access to a whole world of knowledge and imagination, particularly in relation to the rural environment where the pieces, like them, supposedly find their origin. Art and works of art become means by which they themselves can tell the story of their past and thus re-found their history and identity, while giving their existence greater visibility in contemporary society. By bringing out new forms and new aspects of works (illustrating country life with brilliant patinas, in particular) and by associating new uses to them (for interior decoration and collecting, among others), these rec
Keywords: African Research